PENDAMPINGAN PENERAPAN GOOD MANUFACTURING PRACTICE UNTUK PENINGKATAN KUALITAS DAN KEAMANAN PRODUK - Surya Indrawan; Juni S; Sirlyana (Fakultas Teknik, Universitas Samudra, 2023)
Increasing competition in the industrial world, especially in the food sector. With increasing competition, companies or business actors are facing pressure to continue to provide quality products, where customers demand good quality at an affordable price. For this reason, a strategy or method is needed to answer these challenges, one of which is by implementing Good Manufacturing Practice which aims to carry out good production procedures, implementation procedures, control and supervision of the implementation of the production process. Tempe UKM is one of the industrial players in Dumai City which is engaged in the food sector, currently facing intense competition which not only fulfills customer desires and also competition with fellow SMEs. The steps taken are to observe the object that is the target of the service, after that an initial evaluation of the activity is carried out and the last is the socialization activity of mentoring the implementation of Good Manufacturing Practice (GMP).